SM-COLSARSPROT: Highly Immunogenic Supramutational Synthetic Peptides Covering the World’s Population (2022)
ABSTRACT: Fifty ~20–amino acid (aa)–long peptides were selected from functionally relevant SARSCoV-2 S, M, and E proteins for trial B-21 and another 53 common ones, plus some new ones derived from the virus’ main genetic variants for complementary trial C-21. Peptide selection was based on tremendous SARS-CoV-2 genetic variability for analysing them concerning vast human immunogenetic polymorphism for developing the first supramutational, Colombian SARS-protection (SM-COLSARSPROT), peptide mixture. Specific physicochemical rules were followed, i.e., aa predilection for polyproline type II left-handed (PPIIL) formation, replacing b-branched, aromatic aa, short-chain backbone Hbond-forming residues, p-p interactions (n!p* and p-CH), aa interaction with p systems, and molecular fragments able to interact with them, disrupting PPIIL propensity formation. All these modified structures had PPIIL formation propensity to enable target peptide interaction with human leukocyte antigen-DRb1* (HLA-DRb1*) molecules to mediate antigen presentation and induce an appropriate immune response. Such modified peptides were designed for human use; however, they induced high antibody titres against S, M, and E parental mutant peptides and neutralising antibodies when suitably modified and chemically synthesised for immunising 61 major histocompatibility complex class II (MHCII) DNA genotyped Aotus monkeys (matched with their corresponding HLADRb1* molecules), predicted to cover 77.5% to 83.1% of the world’s population. Such chemically synthesised peptide mixture represents an extremely pure, stable, reliable, and cheap vaccine for COVID-19 pandemic control, providing a new approach for a logical, rational, and soundly established methodology for other vaccine development.